PROBLEM OF THE MEASUREMENTS ANGULAR AND LINEAR SIZES OF THE COMPLEX GEOMETRIC FIGURES ON BASE INFORMATION AND MEASURING SYSTEM SIGMA - Leshchenko, Olga; Scherbak, Leonid (Proceedings of National Aviation University (archive), 2006)
Considered problem of the measurement angular and linear sizes large-scale details in aircraft production by means of information and measuring system type Sigma 2030. Motivated use kinematics transformations for decision direct and inverse problem of the kinematics when moving the moving parts IMS in Euclidean space.